Priority landscapes for tree-based restoration in Ethiopia - Pedercini, F.; Dawson, Ian K.; Kindt, R.; Tadesse, W.; Moestrup, S.; Abiyu, A.; Lillesø, Jens-Peter B.; Schoubroeck, F. van; McMullin, S.; Carsan, S.; Mausch, K.; Jamnadass, Ramni; et al. (World Agroforestry Centre, 2021)
The Ethiopian government has set ambitious landscape restoration targets to achieve by 2030. Here, we describe a novel approach to identify landscapes to prioritize for tree-planting-based restoration interventions in the country. Our approach, which has several advantages compared to existing prioritization methods, starts with current land use patterns and potential natural vegetation maps, and uses a wide range of other open-access spatial datasets. The approach estimates the benefits of restoration on prioritized areas compared to a null model where no prioritization is applied. Across identified prioritized landscapes, we then quantify the expected impacts of restoration in terms of the number of households that would be reached by interventions, and by estimating carbon sequestration and soil conservation potentials. Our analysis indicated that Ethiopia has high potential for achieving enhanced restoration targets through landscape prioritization. A total of almost 17 million hectares of land prioritized for tree-based restoration by our exercise could reach 4 million rural households with interventions, with 178 million tonnes of CO2 equivalent sequestered and 160 million tonnes of soil conserved annually. The prioritized landscapes could be restored with a combination of agroforestry, forest enrichment and woodland enrichment practices (on 31%, 8% and 61% of the total prioritized area, respectively). The Oromia region of Ethiopia was identified as a crucial location for intervention, containing almost half of the entire prioritized areas for restoration in the country. Our results provide the foundation for further studies to evaluate the potential impacts of tree-based restoration programmes in Ethiopia, and more widely, as the methods are of general application. Within Ethiopia, investigations in particular support the ex ante impact evaluation of the Provision of Adequate Tree Seed Portfolios project, which is developing national capacity to supply tree seed for restoration purposes. We discuss our findings in this context.